Leadership and Behavior in Humanitarian and Development Transnational Non-Governmental Organizations - Hermann, Margaret G. (2016)
Does leadership matter in the governance of civil society organizations? In particular, do the CEOs of humanitarian and development NGOs exhibit different leadership styles and perceive their work environments in different ways as the literature suggests. To explore this question we interviewed 96 CEOs—32 from humanitarian NGOs and 64 from development NGOs. In the process we found support for the descriptions of the leadership of these two types of organizations extant in the research and practitioner literatures. Those in charge of humanitarian NGOs were more likely to challenge the constraints in their environments, to be interested in influencing what was happening, to want to affect outcomes, and to be focused on addressing the needs of those in the communities facing the crisis, disaster, or emergency. They viewed themselves as having short time in which to respond and chose to communicate and act informally as well as to only collaborate with other organizations if pushed. Providing direct aid and service were high priorities as was advocacy to secure the funding necessary for completing their task. In contrast, CEOs leading development NGOs focused more on respecting and working within the constraints of their positions, being adaptable and flexible in working on having an impact—in effect, being interested in building coalitions and achieving consensus as well as indulging in compromise with the intent of solving the endemic problems that they were there to address. They had a longer time perspective than their humanitarian counterparts and were willing to work within fairly hierarchical structures as well as with a variety of types of collaborators to reach their goals.